MORPHOLOGY OF EXPERIMENTAL BREAST CANCER WITH METASTASIS TO THE LUNGS - Hasanov Komiljon Sunnatillaevich (TADQIQOTLAR, 2025)
Abstract. Metastasis is the final stage of malignant progression; theoretically, a tumor of any size has metastatic potential. The biological nature of cancer and the characteristics of the host determine the possibility of further disease progression even after radical treatment. According to several authors, 12 to 30% of all lung and pleural tumors are metastatic. This review focuses on the comparative morphology of experimental breast cancer with lung metastasis.